1999
DOI: 10.1104/pp.121.3.783
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Gibberellin 20-Oxidase and Gibberellin 3β-Hydroxylase Transcript Accumulation during De-Etiolation of Pea Seedlings

Abstract: Gibberellin (GA) 20-oxidase (GA 20-ox) and GA 3β-hydroxylase (GA 3β-hy) are enzymes that catalyze the late steps in the formation of active GAs, and are potential control points in the regulation of GA biosynthesis by light. We have investigated the photoregulation of the GA 20-ox and GA 3β-hy transcript levels in pea (Pisum sativum L.). The GA 20-oxtranscript level was higher in light-grown seedlings than in etiolated seedlings, whereas GA 3β-hy mRNA accumulation was higher in etiolated seedlings. However, tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
57
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 37 publications
4
57
0
Order By: Relevance
“…Previous studies have shown GAs promote skotomorphogenetic growth of Arabidopsis and pea (Pisum sativum) seedlings grown in darkness (Cowling and Harberd, 1999;Alabadí et al, 2004). Furthermore, a rapid decrease in the levels of bioactive GA 1 has been observed upon transfer of etiolated pea seedlings into light (Ait-ali et al, 1999;Gil and García-Martinez, 2000;O'Neill et al, 2000). Here we have shown that Arabidopsis GA metabolism gene transcript levels change rapidly in response to changes in the light environment.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Previous studies have shown GAs promote skotomorphogenetic growth of Arabidopsis and pea (Pisum sativum) seedlings grown in darkness (Cowling and Harberd, 1999;Alabadí et al, 2004). Furthermore, a rapid decrease in the levels of bioactive GA 1 has been observed upon transfer of etiolated pea seedlings into light (Ait-ali et al, 1999;Gil and García-Martinez, 2000;O'Neill et al, 2000). Here we have shown that Arabidopsis GA metabolism gene transcript levels change rapidly in response to changes in the light environment.…”
Section: Discussionmentioning
confidence: 58%
“…Reed et al, 1996;Ait-ali et al, 1999;Alabadí et al, 2004), none have systematically investigated the role of DELLAs in light-mediated growth regulation. Recent advances have led to the development of Arabidopsis mutant lines that are multiply DELLA deficient and to the use of these lines in experiments that reveal the role of DELLAs in many aspects of plant growth and development, including those that are influenced by environmental conditions (Lee et al, 2002;Cheng et al, 2004;Yu et al, 2004;Cao et al, 2005;Achard et al, 2006).…”
mentioning
confidence: 99%
“…Remarkably, most lightresponsive genes of GA synthesis were also found to be under wavelength-or photoreceptor-specific control. In Arabidopsis, lettuce (Lactuca sativa), and pea (Pisum sativum), light was shown to regulate the expression of GA 3b-hydroxylase and GA 20-oxidase isoforms via either phytochrome-dependent or -independent mechanisms (Toyomasu et al, 1998;Yamaguchi et al, 1998;Ait-Ali et al, 1999;Jackson et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…However, the clearest example of light-regulated hormone biosynthesis during deetiolation comes from pea (Pisum sativum), where transfer of etiolated pea seedlings to light induces a rapid drop in levels of the active GA (GA 1 ), to <10% of dark levels within 4 h (Ait-Ali et al, 1999;Gil and García-Martinez, 2000;O'Neill et al, 2000;Symons and Reid, 2003). This drop is associated with changes in transcript levels of GA biosynthesis genes and depends on the activity of the phyA and cry1 photoreceptors (Reid et al, 2002;Foo et al, 2006).…”
Section: Introductionmentioning
confidence: 99%